2010
DOI: 10.1093/pasj/62.3.709
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Trapped g-Mode Oscillations in Warped Disks around Black Holes

Abstract: In order to study the origin of high-frequency quasi-periodic oscillations observed in X-ray binaries, Kato (2004) suggested a resonant excitation mechanism of disk oscillations in deformed disks. In this paper, we investigate numerically, following his formulation, whether trapped g-mode oscillations in a warped disk, where the warp amplitude varies with radius, can be excited by this mechanism. For simplicity, we adopt Newtonian hydrodynamic equations with relativistic expressions for the characteristic freq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…1) might avoid this damping, but would then have frequencies too high to explain HFQPOs in systems containing black holes with any non-negligible spin angular momentum (Wagoner 2012). On the other hand, lower frequency nonaxisymmetric r-modes lying within their corotation radius do play an ancillary role in the excitation mechanism for m = 0 r-modes considered in this paper (Kato 2004(Kato , 2008Ferreira & Ogilvie 2008;Oktariani et al 2010).…”
Section: Discoseismic Oscillationsmentioning
confidence: 89%
“…1) might avoid this damping, but would then have frequencies too high to explain HFQPOs in systems containing black holes with any non-negligible spin angular momentum (Wagoner 2012). On the other hand, lower frequency nonaxisymmetric r-modes lying within their corotation radius do play an ancillary role in the excitation mechanism for m = 0 r-modes considered in this paper (Kato 2004(Kato , 2008Ferreira & Ogilvie 2008;Oktariani et al 2010).…”
Section: Discoseismic Oscillationsmentioning
confidence: 89%
“…Related to this subject, Kato (2004Kato ( , 2008a suggested that a pair of positive-and negative-energy oscillations can be excited in deformed (warped or eccentric) disks by their resonant interaction through disk deformation. The presence of this excitation mechanism seems to be confirmed by numerical calculations (Ferreira and Ogilvie 2008;Oktariani et al 2010) and by analytical examinations (Kato et al 2011) made by a different method from Kato's original one.…”
Section: Introductionmentioning
confidence: 77%
“…Finally, as an application of the present resonant excitation process of oscillations, we briefly note Kato's model of high-frequency twin QPOs (e.g., Kato and Fukue 2006). In this model the lower-frequency QPO of the twin is related to the set of g-mode and p-mode os-cillations considered numerically by Ferreira and Ogilvie (2008) and Oktariani et al (2010). The higher-frequency QPO of the twin is considered to be the set of one-armed g-mode and two-armed p-mode oscillations [see for details figures 1 to 3 of Kato (2008a)].…”
Section: Discussionmentioning
confidence: 96%
“…First, let us describe, in terms of the present formulation, the g-and p-modes resonant instability that was numerically studied by Ferreira and Ogilvie (2008) and Oktariani et al (2010). They considered the resonant interaction, through a standing warp (ω D = 0), between i) the axisymmetric g-mode oscillation whose ξ r has one node in the vertical direction and ii) the one-armed p-mode oscillation whose ξ r has no node in the vertical direction.…”
Section: Discussionmentioning
confidence: 99%